The effect of fins on PCM containers on solar panel cooling performance - Seto, D.B.; Yahya, W.; Ramelan, U. (Dinamika Teknik Mesin, 2025)
Solar energy is a renewable energy source that is abundant and emits low emissions. The operating temperature of a solar panel has a significant impact on its efficiency. A 50 Wp polycrystalline solar panel was tested in this experiment using PCM (paraffin) as a passive cooling solution and without it. The PCM was placed on the backplate of the solar panel using a container equipped with fins to enhance cooling efficiency. Simulations were conducted using a solar simulator with varying light intensities of 470 W/m², 650 W/m², 900 W/m², and 1000 W/m², while a blower was used to simulate constant airflow around the surrounding area.Evaluating the panel temperature and calculating the error rate in experimental findings were the goals of the simulation. According to the simulation, the average temperature of a solar panel without cooling reached 59.4°C at an intensity of 1000 W/m2, but the temperature dropped to 57.8°C and 55.4°C, respectively, when PCM cooling with 5 and 10 fins was used.This experiment demonstrated that the application of PCM with a modified container can lower the maximum temperature of the solar panel and increase its maximum efficiency by 1.15% at an intensity of 1000 W/m². This passive cooling system has proven to be effective in reducing the operational temperature of solar panels.